Solid solution tungsten carbide powder and application thereof
By adding chromium into tungsten carbide to form a solid solution phase, combined with metal binder and additives, the problem of deterioration and thermal conductivity of cemented carbide is solved, and the high-temperature oxidation resistance of tungsten carbide powder is achieved Improved, suitable for liquid batteries and other applications.
Patent Information
- Application Number
- CN202410920506.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-17
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-17
AI Technical Summary
When the existing carbide compositions improve the deformation resistance of cemented carbides, they usually lead to a decrease in toughness and thermal conductivity, making it difficult to improve oxidation resistance while maintaining hardness and wear resistance.
By adding chromium (Cr) to tungsten carbide (WC) to form a (W,Cr) solid solution phase, and combining metal binder and additives, tungsten carbide powder and ready-to-press powder with enhanced oxidation resistance are prepared. Used to manufacture cemented carbide products with improved performance.
It significantly improves the oxidation resistance of tungsten carbide powder, especially in high temperature environments, reduces oxidation and weight gain, and is suitable for liquid batteries and other oxidation-resistant environment applications.
Smart Images

Figure CN119320139A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to tungsten carbide powder, and in particular to tungsten carbide powder including a (W,Cr)C solid solution. Background Art
[0002] The properties of metal carbide compositions have been studied for a long time. For example, cutting tool manufacturers have examined the composition changes of carbide compositions and the impact on cemented carbide properties (including but not limited to hardness, wear resistance, heat deformation resistance, toughness and density) thereof. However, the enhancement of one carbide property usually leads to the accompanying degradation of another cemented carbide property. For example, improving the deformation resistance of cemented carbide can lead to a reduction in toughness and thermal conductivity. However, in order to meet the ever-changing needs of metal processing and other industrial applications, the carbide body must be improved, and when the carbide composition is subjected to composition changes, it is necessary to carefully balance the competing properties to strive to provide products with improved performance. Summary of the invention
[0003] In one aspect, tungsten carbide compositions that exhibit enhanced oxidation resistance are described herein. In some embodiments, the tungsten carbide powder includes a (W, Cr) C solid solution phase. As further described herein, incorporation of chromium (Cr) into the tungsten carbide (WC) lattice can improve the oxidation resistance of WC, including high temperature oxidation resistance in air. In some embodiments, the amount of chromium in the (W, Cr) C powder can be at least 1 wt.%, at least 5 wt.%, or at least 10 wt.%.
[0004] The tungsten carbide powder can be formed by carburizing a mixture comprising tungsten powder, carbon powder, and chromium powder components. In some embodiments, the chromium component is chromium oxide, such as Cr 2 O 3 For example, the carburized powder mixture may include 1 wt.% or more Cr 2 O 3 、5wt.% or more Cr 2 O 3 , or 10wt.% or more Cr 2 O 3 .
[0005] In another aspect, a ready-to-press (RTP) powder comprising a solid solution tungsten carbide powder (W, Cr) C is described. In addition to the solid solution tungsten carbide powder (W, Cr) C, the RTP powder also includes a metal binder and one or more optional additives. In embodiments where the RTP powder includes one or more additives, the metal binder may be iron (Fe), cobalt (Co), nickel (Ni), or alloys thereof. The one or more additives may be selected from vanadium carbide (VC), chromium carbide (Cr3 C 2 ), rhenium (Re), ruthenium (Ru), molybdenum carbide (Mo 2 C) and combinations thereof. In some embodiments, the one or more additives may include a grain growth inhibitor.
[0006] In another aspect, an article made from the RTP powder disclosed herein is provided. The article may be a seal for a liquid battery or other article subjected to an oxidative environment.
[0007] Also described is a liquid battery including a seal made from the RTP powder disclosed herein.
[0008] In another aspect, a manufacturing method is provided. In some embodiments, the manufacturing method may have one or more of the following steps. For example, the manufacturing method may include the following steps: carburizing a mixture of tungsten powder, carbon powder, and a chromium component to form a tungsten carbide powder including a (W,Cr)C solid solution phase. In some embodiments, the chromium component is chromium oxide, such as Cr 2 O 3 In some embodiments, the powder mixture for carburization may include at least 1 wt.% Cr 2 O 3 、at least 5wt.% Cr 2 O 3 , or at least 10wt.% Cr 2 O 3 Another step of the manufacturing method may include forming a ready-to-press (RTP) powder from the solid solution phase tungsten carbide powder. The RTP powder may be used to form a cemented carbide component.
[0009] These and other embodiments are further described in the detailed description which follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a graph showing weight gain (%) in a 600°C oven over a 6 hour period for certain embodiments described herein. CSM1 is compared to CBM1.
[0011] Figure 2 is a graph showing weight gain (%) in a 600°C oven over a 6 hour period for certain embodiments described herein. CSM2 is compared to CBM2.
[0012] Figure 3 is a graph showing weight gain (%) in a 600°C oven over a 6 hour period for certain embodiments described herein. CSM3 is compared to CBM3.
[0013] Figure 4 is a graph showing weight gain (%) in a 600°C oven over a 6 hour period for certain embodiments described herein. CSM4 is compared to CBM4.
[0014] Figure 5 is a graph showing weight gain (%) after 6 hours and 24 hours of oxidation for certain examples described herein.
[0015] Figure 6 is a graph showing the weight gain (%) after 24 hours of oxidation for certain examples described herein. Comparison of CSM1 and CBM1.
[0016] Figure 7 is a graph showing the weight gain (%) after 24 hours of oxidation for certain examples described herein. Comparison of CSM2 and CBM2.
[0017] Figure 8 Depicted is a sintered hard metal component oxidized at 850°C in air for 24 hours.
[0018] Fig. 9 is the XRD spectrum of CSM1 powder.
[0019] Fig.10 is the XRD spectrum of CSM2 powder.
[0020] Fig.11 is the XRD spectrum of oxidized CSM2 powder (850°C, 24 hours).
[0021] Fig.12 Contains XRD spectra of CSM4 powder and oxidized CSM4 powder (850°C for 24 hours).
[0022] Fig.13 is a schematic diagram of an exemplary liquid battery. DETAILED DESCRIPTION
[0023] By referring to the following detailed description and examples and its previous and following description, the embodiments described herein can be more easily understood. However, the elements, devices and methods described herein are not limited to the specific embodiments presented in the detailed description and examples. It should be appreciated that these embodiments are merely illustrations of the principles of the present invention. Without departing from the spirit and scope of the present invention, many modifications and adaptations will be apparent to those skilled in the art.
[0024] Solid Solution Tungsten Carbide Powder
[0025] Tungsten carbide powder described herein includes (W, Cr) C solid solution phase. As understood by those skilled in the art, solid solution is a mixture of two crystalline solids coexisting in the form of a new crystalline solid or lattice. The term "solution" is used to describe the intimate mixing of components at the atomic level, and is different from the physical mixture of components. The amount of chromium in the solid solution tungsten carbide powder (W, Cr) C can be 1wt.% or more, 5wt.% or more, or 10wt.% or more. 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.% or 20wt.% can be particularly preferred. In some embodiments, the carbon content of tungsten carbide powder can be between 5wt.% and 15wt.%.
[0026] Tungsten carbide powder can be formed by carburizing a mixture comprising, consisting of, or consisting essentially of: a black mix and chromium oxide, such as Cr 2 O 3 Typically, the black mixture includes, consists of, or consists essentially of: tungsten powder and carbon powder. In some embodiments, the black mixture may further include, consist of, or consists essentially of: Cr in an amount less than about 1 wt.% of the black mixture. 2 O 3 . Carburized mixture (black mixture + Cr 2 O 3 ) may include 1wt.% or more Cr 2 O 3 、5wt.% or more Cr 2 O 3 , or 10wt.% or more Cr 2 O 3 In some embodiments, Cr 2 O 3 The maximum amount of Cr is about 20 wt.%. It is believed that Cr above 1 wt.%, preferably above 5 wt.%, and most preferably above 10 wt.% 2 O 3 The amount of Cr is necessary to give the obtained solid solution tungsten carbide powder the desired oxidation resistance. 2 O 3 However, it is contemplated that other chromium oxides may also be used to provide the (W,Cr)C solid solution powder.
[0027] The amount of carbon in the carburized mixture can be about 1 wt.% to about 15 wt.%, about 2 wt.% to about 10 wt.%, about 3 wt.% to about 10 wt.%, about 4 wt.% to about 10 wt.%, about 5 wt.% to about 10 wt.%, about 6 wt.% to about 10 wt.%, about 7 wt.% to about 10 wt.%, about 8 wt.% to about 10 wt.%, or about 9 wt.% to about 10 wt.%.
[0028] As will be appreciated by those skilled in the art, carburizing is the process of converting tungsten metal powder into tungsten carbide by reacting with carbon powder in a furnace. Suitable carburizing conditions are not limited thereto. Typical carburizing temperatures may be between about 1300° C. and 2650° C. Carburizing is typically performed in a hydrogen atmosphere.
[0029] Ready-to-press or graded powder
[0030] Also disclosed herein is a ready-to-press (RTP) or graded powder. The RTP powder may include, consist of, or consist essentially of: (1) a solid solution (W,Cr)C powder as disclosed above, (2) a metal binder, and (3) one or more optional additives. The composition of the RTP powder may be varied to provide a conventional grade, a corrosion resistant grade, or a heat resistant grade.
[0031] The metal binder is not limited thereto and may include Fe, Co, Ni or alloys thereof. The metal binder may be present in the RTP powder in any desired amount. In some embodiments, the metal binder is present in an amount of 3-15 wt.% or 6-10 wt.% of the powder composition. In some preferred embodiments, the RTP or graded powder may include about 6% nickel binder.
[0032] The one or more optional additives are also not limited thereto. The one or more additives may be selected from VC, Cr 3 C 2 ,Re,Ru,Mo 2 C and combinations thereof. In some embodiments, the one or more additives may include one or more grain growth inhibitors. As will be appreciated by those skilled in the art, grain growth inhibitors are used to control grain growth during hot working and densification of RTP powders. Examples of suitable grain growth inhibitors include, but are not limited to, VC, Cr 3 C 2 、NbC、TaC、Mo 2C, titanium carbide (TiC) and tantalum niobium carbide (TaNbC). The amount of grain growth inhibitor can be about 0.1 to 5 wt.% of the powder composition. Optional components, including other metal carbide species, are added after the solid solution powder (W,Cr)C is formed. Therefore, such optional components (when present) are mixed with the solid solution powder (W,Cr)C to obtain RTP powder.
[0033] In some embodiments, the solid solution powder (W,Cr)C accounts for 70 to 97 weight percent of the RTP powder, and in some embodiments, the grain size of the (W,Cr)C grains can be in the range of 0.4 microns to 10 microns. The components of the RTP powder can be ground, spray dried, and / or sieved to form the final RTP powder.
[0034] Cemented carbide products
[0035] RTP powder can be used to produce a variety of cemented carbide products, including tools, consumable parts, battery components and other industrial products. In particular, the formed products can be used in environments where oxidation resistance is desired at high temperatures (e.g., up to 500°C). An example of such a component is a seal for a liquid battery. As those skilled in the art will appreciate, liquid batteries are different from other types of batteries. For example, their electrodes typically include molten metals, and the electrolyte that conducts current between them is typically a molten salt. Fig.13 An exemplary liquid battery cell is shown in FIG.
[0036] The negative electrode material may include one or more selected from Li, Na, Mg, K, Ca, Rb, Sr, Cs and Ba. In some preferred embodiments, the negative electrode may include Ca. The positive electrode material may include one or more selected from Zn, Ga, Cd, In, Sn, Sb, Te, Hg, Hg, Tl, Pb and Bi. In some preferred embodiments, the positive electrode may include Sb.
[0037] Manufacturing method
[0038] Also provided herein are methods of making (W,Cr)C solid solution powders and associated RTP powders.
[0039] In one aspect, a method for preparing a (W,Cr)C solid solution powder comprises, consists of, or consists essentially of: mixing carbon powder and tungsten powder with chromium oxide powder (such as Cr 2 O 3The powders are mixed to form a powder mixture. A ball mill, a grinding mill, or a special blender can be used to achieve the mixing. For example, a blender that allows rotation, translation, and / or inversion during the entire mixing process. In addition, the mixing of the various powders can be applied at room temperature for a sufficient period of time to achieve a uniform or substantially uniform distribution of the components of the mixture. For example, the mixing time can vary from about two hours to about twenty-four hours. In a preferred embodiment, the resulting mixed powder includes more than 1 wt.% Cr 2 O 3 、Cr over 5wt.% 2 O 3 , or more preferably more than 10wt.% Cr 2 O 3 .
[0040] The obtained powder mixture (comprising carbon powder, tungsten powder and Cr 2 O 3 Carburizing is a process of converting tungsten metal powder into tungsten carbide by reacting with carbon powder in a furnace. Suitable carburizing conditions are not limited thereto. Typical carburizing temperatures may be between about 1300°C and 2650°C. Carburizing is usually performed in a hydrogen atmosphere.
[0041] On the other hand, the solid solution (W, Cr) C powder is combined with a powder metal binder and optional additives to produce the RTP or graded powder described herein. The RTP powder for cemented carbide product manufacturing can be prepared using established grinding and spray drying processes. For example, a slurry of tungsten carbide powder, metal binder, inhibitor and solvent can be ground. The solvent is not limited to this and can be water or an organic liquid such as heptane or acetone. After grinding, the solvent is removed by drying using a spray dryer or a vacuum dryer. In the spray drying process commonly used in the cemented carbide industry, a hot inert gas such as nitrogen is impacted with a stream of carbide particles. In a preferred embodiment, a solid lubricant such as paraffin is added to the powder at the end of or after the grinding process.
[0042] In other aspects, RTP or graded powders described herein are used to form cemented carbide products. RTP can be consolidated into a desired green product shape and then sintered. Known forming techniques include but are not limited to pellet pressing, uniaxial pressing, cold isostatic molding, injection molding, extrusion and / or additive manufacturing. Alternatively, RTP powder can be deposited and sintered in a layer-by-layer process (e.g., in an additive manufacturing technique including selective laser sintering, selective laser melting or electron beam melting). Post-sintering operations can also be performed after pressure-free or pressure-assisted sintering (sintering-HIP). These include but are not limited to hot isostatic molding and post-sintering forming.
[0043] These and other embodiments are further described in the following non-limiting examples.
[0044] Examples
[0045] Make black mixture with Cr 2 O 3 The powder and the carbon powder are co-carburized to form a (W,Cr)C solid solution powder.
[0046] The composition of the black mixture is as follows:
[0047] Black mixture 1 (BM1) - 93.223 wt. % W, 6.19 wt. % C, 0.587 wt. % Cr 2 O 3 .
[0048] Black mixture 2 (BM2) - 93.316 wt. % W, 6.18 wt. % C, 0.504 wt. % Cr 2 O 3 .
[0049] Black mixture 3 (BM3) - 93.223 wt. % W, 6.19 wt. % C, 0.587 wt. % Cr 2 O3
[0050] Black mixture 4 (BM4) - 93.223 wt. % W, 6.19 wt. % C, 0.587 wt. % Cr 2 O3
[0051] The sample mixture is formed from the black mixture:
[0052] Sample mixture 1 (SM1): 14.9119 kg of black mixture 1 (BM1) and 2.9985 kg of Cr 2 O3 mixed to form a calculated 77.62% W, 5.15% C and 17.23% Cr 2 O 3 The weight percentage of the mixed powders was used to form the sample mixture 1. The blender was used for mixing in batches, each batch lasting 1 hour. The mixing was carried out at room temperature.
[0053] Sample mixture 2 (SM2): 14.8726 kg of black mixture 2 (BM2) and 2.8861 kg of Cr 2 O 3 and 1.478 kg of C to form a molten-liquid phase having a calculated content of 72.17% W, 15.4% Cr 2 O 3 and 12.44% C by weight to form sample mixture 2. The blender was used for mixing in batches, each batch lasting 1 hour. The mixing was carried out at room temperature.
[0054] Sample Mix 3 (SM3) - Sample Mix 3 was formed using Black Mix 3 (BM3). A SM3 was formed with a calculated W of 72.92, 15.26% Cr 2 O 3 and 11.82% C by weight. The blender was used for mixing in batches, each batch lasting 1 hour. The mixing was carried out at room temperature.
[0055] Sample Mix 4 (SM4) - Black Mix 4 (BM4) was used to form Sample Mix 4. A calculated 83.38% W, 7.10% Cr 2 O 3 and 9.52% C by weight. The blender was used for mixing in batches, each batch lasting 1 hour. The mixing was carried out at room temperature.
[0056] The mixture compositions of the black mixtures (BM1, BM2, BM3 and BM4) and the sample mixtures (SM1, SM2, SM3 and SM4) are also shown in tabular form in Table 1 below:
[0057] Table 1
[0058] SM1 BM1 SM2 BM2 SM3 BM3 SM4 BM4 W (wt.%) 77.62 93.223 72.17 93.316 72.92 93.223 83.38 93.223 <![CDATA[Cr 2 O 3 (wt.%)]]> 17.23 0.587 15.4 0.504 15.26 0.587 7.10 0.587 C (wt.%) 5.15 6.19 12.44 6.18 11.82 6.19 9.52 6.19
[0059] Then, sample mixture 1 (SM1), sample mixture 2 (SM2), sample mixture 3 (SM3), and sample mixture 4 (SM4) were carburized in a hydrogen atmosphere to form carburized sample mixture 1 (CSM1), carburized sample mixture 2 (CSM2), carburized sample mixture 3 (CSM3), and carburized sample mixture 4 (CSM4). Carburization forms a solid solution phase (W, Cr) C, in which chromium (Cr) has been incorporated into the crystal structure of tungsten carbide (WC).
[0060] Carburized sample mixture 1 (CSM1) was tested and found to contain 1.87% carbon, 11.03% chromium and 0.234% oxygen with the balance being tungsten. The XRD spectrum of the CSM1 powder can be seen at Fig. 9 . Cr levels reported in the NSL assay were tested.
[0061] Carburized sample mixture 2 (CSM2) was tested and found to have 9.37% carbon, 11.94% chromium, 0.0358% oxygen and the balance tungsten. The XRD spectrum of the CSM2 powder can be seen at Fig.10 . Cr levels reported in the NSL assay were tested.
[0062] Carburized sample mix 3 (CSM3) was tested and found to have 9.57% carbon, 9.99% chromium and 0.0591% oxygen with the balance being tungsten. The reported Cr levels were tested in the NSL analysis.
[0063] Carburized sample mixture 4 (CSM4) was tested and found to have 7.81% carbon, 5.00% chromium and 0.0684% oxygen with the balance being tungsten. The XRD spectrum of CSM4 can be seen at Fig.12 . Cr levels reported in the NSL assay were tested.
[0064] The black mixture (BM1, BM2, BM3, BM4) is also carburized to form a carburized black mixture (CBM1, CBM2, CBM3, and CBM4).
[0065] A comparison of the analytical chemical properties of the carburized sample mixtures (CSM1, CSM2, CSM3 and CSM4) and the carburized black mixtures (CBM1, CBM2, CBM3, CBM4) is presented in Table 2 below:
[0066] Table 2
[0067] CSM1 CBM1 CSM2 CBM2 CSM3 CBM3 CSM4 CBM4 Carbon (wt.%) 1.87 6.12 9.37 6.12 9.57 6.11 7.81 6.09 Chromium (wt.%) 11.03 0.40 11.94 0.32 9.99 0.38 5.00 0.38 Oxygen (wt.%) 0.234 0.107 0.0358 0.1037 0.0591 0.1085 0.0684 0.1144
[0068] Oxidative Weight Gain Studies
[0069] Oxidation weight gain research is carried out by comparing carburized sample mixture 1 (CSM1) with carburized black mixture 1 (CBM1) and comparing carburized sample mixture 2 (CSM2) with carburized black mixture 2 (CBM2). Six samples are placed in a furnace of 600 degrees Celsius. Take out a sample and test each hour in a total of six hours. The data of comparing carburized black mixture 1 (CBM1) and carburized sample mixture 1 (CSM1) can be found in the following table 3:
[0070] Table 3
[0071]
[0072] This data is also shown graphically in Figure 1 Where (W,Cr)C refers to carburized sample mixture 1 (CSM1), and CBM1 is carburized black mixture 1 (CBM1). Figure 1 As shown, the oxidation weight gain of carburized sample mixture 1 (CSM1) is up to 44% lower than that of carburized black mixture 1 (CBM1).
[0073] Data comparing carburized black mixture 2 (CBM2) and carburized sample mixture 2 (CSM2) can be found in Figure 2, where (W,Cr)C refers to carburized sample mixture 2 (CSM2), and CBM2 is carburized black mixture 2 (CBM2). Figure 2 As shown, the oxidation weight gain of carburized sample mixture 2 (CSM2) is up to about 30% lower than the oxidation weight gain of carburized black mixture 2 (CBM2).
[0074] Data comparing carburized black mixture 3 (CBM3) and carburized sample mixture 3 (CSM3) can be found in Figure 3 , where (W,Cr)C refers to carburized sample mixture 3 (CSM3), and CBM3 is carburized black mixture 3 (CBM3). Figure 3 As shown, the oxidation weight gain of carburized sample mixture 3 (CSM3) is up to about 25% lower than the oxidation weight gain of carburized black mixture 3 (CBM3).
[0075] Data comparing carburized black mixture 4 (CBM4) and carburized sample mixture 4 (CSM4) can be found at Figure 4 , where (W,Cr)C refers to carburized sample mixture 4 (CSM4), and CBM4 is carburized black mixture 4 (CBM4). Figure 4 As shown, the oxidation weight gain of carburized sample mixture 4 (CSM4) is up to about 21% lower than the oxidation weight gain of carburized black mixture 4 (CBM4).
[0076] Overnight oxidation studies
[0077] Overnight oxidation studies were also performed on carburized sample mixture 1 (CSM1). Six samples were weighed into crucibles and placed in an oven at 850°C. The samples were removed after 24 hours of treatment, cooled and weighed. The resulting mass increase was compared to the initial mass of the sample to obtain a percentage. The data from this experiment can be found in Table 4 below.
[0078] Table 4
[0079]
[0080] Figure 5 The oxidative weight gain of CSM1-1 through CSM1-6 (identified as "(W,Cr)C: 6 hours") from Table 3 is graphically depicted compared to the oxidative weight gain of samples CSM1-1-24 through CSM1-6-24 (identified as "(W,Cr)C: 24 hours"). For the more severe overnight oxidation test (24 hours), the oxidative weight gain is still lower.
[0081] Overnight oxidation studies were also conducted on carburized black mixture 1 (CBM1), and Figure 6The graph in compares the weight gain (%) of CSM1 (identified as (W,Cr)C) and CBM1 (identified as CBM1).
[0082] Overnight oxidation studies were also conducted on carburized black mixture 2 (CBM2) and carburized sample mixture 2 (CSM2). Figure 7 The graph in compares the weight gain (%) of CSM2 (identified as (W,Cr)C) and CBM2 (identified as CBM2).
[0083] like Figure 6 and Figure 7 As shown, the more severe overnight oxidation test showed lower oxidation for the carburized sample mixes (e.g., CSM1 and CSM2) compared to the carburized black mixes (e.g., CBM1 and CBM2). Samples 1 to 4 showed higher oxidation than the corresponding CBM1 sample, which may be due to the relatively low carbon content of CSM1. Tungsten or low carburized WC is more easily oxidized than fully carburized WC. The very low carbon content of CSMI also makes it difficult to produce uniformly carburized particles, which may explain the Figure 6 In contrast, CSM2 has a higher carbon content with a lower and more consistent oxidation weight gain compared to CSM1 ( Figure 7 ). This emphasizes the importance of carbon content in addition to Cr content in the oxidation resistance of WC.
[0084] Ready-to-press (RTP) powder
[0085] The carburized sample mixture 4 (CSM4) powder was then mixed with Co or Ni using an established grinding and spray drying process to prepare ready-to-press (RTP) powder for component manufacturing. The formulation mixture of the RTP powder is shown in Table 5 below:
[0086] Table 5
[0087]
[0088] A control batch of GU-108572 was also formed. The formulation mixture of the control batch is shown in Table 6 below:
[0089]
[0090] Figure 8 Contains depictions of sintered hard metal parts made of GU-108572RTP1 and RTP2, respectively, oxidized in air at 850°C for 24 hours. The weight gain of GU-108753 is 18.92%. The weight gain of RTP1 is 16.36%. The weight gain of RTP2 is 17.03%.
[0091] Table 7 below contains the sintering properties of parts made using RTP1, RTP2 and GU-108572 under the following sintering conditions: 1475°C for 90 minutes, vacuum sintering.
[0092] Table 7
[0093]
[0094] Components made using ready-to-press (RTP) powders can be seals for liquid battery cells, such as Fig.13 shown.
[0095] In order to achieve various purposes of the present invention, various embodiments of the present invention have been described. It should be appreciated that these embodiments are merely illustrations of the principles of the present invention. Many modifications and adaptations thereof will be apparent to those skilled in the art without departing from the spirit and scope of the present invention.
Claims
1. A tungsten carbide powder comprising a (W,Cr)C solid solution phase.
2. The tungsten carbide powder according to claim 1, comprising more than 1 wt.% chromium based on the total weight of the powder.
3. The tungsten carbide powder of claim 1, comprising at least 5 wt. % chromium based on the total weight of the powder.
4. The tungsten carbide powder of claim 1, comprising at least 10 wt. % chromium based on the total weight of the powder. The tungsten carbide powder according to claim 1 , wherein the average grain size thereof is 0.4 μm to 10 μm.
6. The tungsten carbide powder of claim 1, wherein carbon is present in an amount of 1-10 wt% of the powder.
7. The tungsten carbide powder of claim 1, wherein carbon is present in an amount of 5-10% by weight of the powder.
8. The tungsten carbide powder according to claim 1, comprising 5-15 wt% chromium, 1-10 wt% carbon and the balance tungsten.
9. A ready-to-press (RTP) powder comprising: Tungsten carbide powder, the tungsten carbide powder comprising a (W, Cr) C solid solution phase, Metal adhesive.
10. The RTP powder according to claim 9, wherein the metal binder is Fe, Co, Ni or an alloy thereof.
11. The RTP powder of claim 9, further comprising one or more additives.
12. The RTP powder according to claim 11, wherein the one or more additives are selected from VC, Cr3C2, Re, Ru, Mo2C and combinations thereof.
13. The RTP powder of claim 11, wherein the one or more additives comprises a grain growth inhibitor.
14. A cemented carbide product formed from the RTP powder according to claim 9.
15. The cemented carbide article of claim 14, wherein the component is a seal for a liquid battery.
16. A liquid battery comprising the assembly according to claim 15.
17. A manufacturing method, comprising: A mixture of tungsten powder, carbon powder and chromium oxide is carburized to form a tungsten carbide powder including a (W,Cr)C solid solution phase, wherein the mixture includes at least 1 wt. % of the chromium oxide.
18. The manufacturing method according to claim 17, wherein the mixture comprises at least 5 wt.% of the chromium oxide.
19. The manufacturing method according to claim 17, wherein the chromium oxide is Cr2O3.
20. The method of manufacturing according to claim 17, further comprising combining the tungsten carbide powder comprising the (W,Cr)C solid solution phase with a powder metal binder and optional additives to provide a ready-to-press (RTP) powder.
21. The manufacturing method according to claim 20, wherein the ready-to-compact powder is used to form a cemented carbide product.